An Efficient Synthesis of 1,8-Dioxo-Octahydroxanthenes Derivatives Using Heterogeneous Ce-ZSM-11 Zeolite Catalyst - Rameshwar R. Magar; Ganesh T. Pawar; Sachin P. Gadekar; Machhindra Karbhari Lande (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
The Ce-ZSM-11 zeolite has been used as an efficient catalyst for the one pot synthesis of 1,8-dioxo-octahydroxanthene derivatives from aromatic aldehyde and 5,5-dimethyl-cyclohexane-1,3-dione under reflux condition. The catalyst was characterized by Powder X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), Fourier Transform Infrared Spectroscopy (FTIR), Brunauer-Emmer-Teller (BET) surface area analysis, and Temperature Programmed Desorption (TPD) techniques. This method provides several advantageous such as use of inexpensive catalyst, simple work-up procedure, high yield of desired product and reusability of catalyst.